ミズホキチ ニ オケル ヒョウショウ ヒョウソウ ブ ノ Pハ Sハ ノ ソクド ソクテイ - 石沢, 賢二; イシザワ, ケンジ; Ishizawa, Kenji (1981)
P(論文) 南極大陸氷床上部のP波とS波の速度が, みずほ基地(70°42'S, , 44°20'E, , 海抜2230m)において測定された。測定方法は, 12・13次日本南極地域観測隊で掘削されたボーリング孔を使用した検層と, 屈折法である。検層には孔中固着式受震器が使用され, 深さ80mまでのP波S波の速度構造が求められた。また屈折法ではP波の構造が36mまで測定された。得られた結果は, コアーを使用した超音波パルス法による測定結果とほぼ同じであった。南極やグリーンランドのさまざまな場所で得られたP波の速度構造を対比してみた結果, その場所での年平均気温と強い相関があることがわかった。深さ50mのP波速度に注目してみると, 年平均気温, T_m (℃), が高いほどP波の速度, V_P (km/s), は大きく, それらの間には次のような関係がある。V_P=0.034T_m+4.529 The measurements of P and S wave velocity in the surface layer down to a depth of 80m were made at Mizuho Station (70°42'S, 44°20'E, 2230m a.s.l.) in 1978 by the following method : one was a borehole logging and the other was a refraction. The variation of the velocity with depth was obtained and it was found that the velocity obtained in the measurement was approximately equal to that obtained experimentally in a laboratory using the core samples drilled at Mizuho Station. The data of P wave velocity measured in Antarctica and Greenland were summarized and the relationship between the P wave velocity at a depth of 50m, V_P, and the mean annual temperature, T_m, was obtained as follows : V_P=0.034T_m+4.529(km/s). departmental bulletin paper